Communication management in promoting knowledge and creativity in fostering innovations in the creative organizations - Atkočiūnienė, Zenona Ona; Siudikienė, Daiva (Creativity Studies, 2021)
The topic of innovation is extremely important because it relates to the ability of organizations, urban regions and even states to remain competitive in today’s rapidly changing world. The problem for modern organizations is how to increase the scale and efficiency of innovation in modern organizations. One of the most striking modern trends that helps to generate innovation is the involvement of the organization’s stakeholders in the processes of value co-creation, encouraging their processes of collective cooperation, knowledge sharing and creative expression. Changing value creation processes are becoming a critical factor in creating innovation. Value creation has always been an essential foundation of any organization’s activities, but the targeted involvement of stakeholders in value creation is a relatively new phenomenon. The article presents a study, the aim of which is to investigate how and in what forms creative organizations – publishing houses – use the adaptability of their managed communication channels to encourage stakeholder involvement in value co-creation processes in innovation. Stakeholder involvement in the development of new ideas and projects, networking, collaboration, knowledge sharing, various non-formal learning opportunities, creation of discussion and feedback platforms as important drivers of stakeholder engagement are particularly important in fostering value-added processes in innovation.